2019
DOI: 10.1155/2019/4145721
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study and Field Monitoring of the Ground Deformation Induced by Large Slurry Shield Tunnelling in Sandy Cobble Ground

Abstract: This paper presents the ground deformation induced by the large slurry shield tunnelling with a diameter of about 12 m in urban areas, which may challenge the safety of the existing nearby constructions and infrastructures. In this study, the ground deformation is analyzed by a three-dimensional finite difference model, involving the simulation of tunnelling advance, grouting, and grouting hardening. The transverse settlement, longitudinal settlement, and horizontal displacement of the ground are analyzed by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…e montmorillonite content of the bentonite used in the experiment was 63.35%. e density of the bentonite suspension was 1.01 g/cm 3 , and the bentonite content was 9.2%. Silt sand particles were screened by vibrating screen into three different particle groups, and the particle size range is <75 μm, 75 μm∼100 μm, and 100 μm∼150 μm.…”
Section: Experimental Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…e montmorillonite content of the bentonite used in the experiment was 63.35%. e density of the bentonite suspension was 1.01 g/cm 3 , and the bentonite content was 9.2%. Silt sand particles were screened by vibrating screen into three different particle groups, and the particle size range is <75 μm, 75 μm∼100 μm, and 100 μm∼150 μm.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Large-diameter slurry shields are widely used in urban tunnel engineering and sea-(or river-) crossing traffic tunnel engineering [1][2][3]. During shield construction, the mud slurry penetrates soil and forms a mud filtration cake on the excavation surface, which can balance the pressure of water and soil in the ground; thus, the excavation surface is stabilized.…”
Section: Introductionmentioning
confidence: 99%
“…According to the inspection results of double-arch tunnels in Sichuan and Chongqing, the depth or height of voids behind the lining generally ranged from 0.15 to 0.50 m, and the maximum value reached 1.09 m [19]. In practical engineering, field monitoring remains a generally recognized approach for understanding the deformation of the ground and the neighboring structures [20][21][22], whereas there are numerous voids with different sizes developed around the double-arch tunnel lining. Different arrangements and sizes of voids can change stress, deformation, and failure of the lining.…”
Section: Numerical Schemesmentioning
confidence: 99%
“…Li [4] analyzed the effects of excavation method, reserved bench length, advanced support, and tunnel burial depth on ground settlement based on the Harbin subway tunnel. Zhang et al [5] used a three-dimensional finite difference model to simulate the advance grouting and grouting hardening of the shield tunnel and compared it with the field measurement data to analyze the lateral settlement, longitudinal settlement, and horizontal displacement of the ground. It is concluded that the lateral settlement occurs at about 1.5 times of the excavation diameter.…”
Section: Introductionmentioning
confidence: 99%